Reactive and Functional Nanoobjects by Polymerization‐Induced Self‐Assembly. Issue 2 (16th October 2018) - Le, Dao; Keller, Dominic; Delaittre, Guillaume
Abstract: Polymerization‐induced self‐assembly (PISA) is becoming a standard technique for generating core–shell polymeric nanoparticles of various morphologies ranging from classic spheres to rods/fibers ("worm‐like") and vesicles. After the initial quest for polymerization control in dispersed media, the focus of PISA research has drastically shifted, first to morphological control and now to the introduction of reactivity and functionality in order to generate useful materials. The present review is dedicated to the latter aspect. Reactivity is distinguished from functionality such as complexing, templating, and catalyzing. Approaches for either shell or core functionalization are also detailed separately. Abstract : Nanoobjects obtained by polymerization‐induced self‐assembly and possessing a shell and/or a core that are either reactive or performing a function are discussed. Specific initiators, transfer agents, and monomers are described for providing access to small‐molecule attachment, crosslinking, nucleation of inorganic nanomaterials, recognition, and biocidal activity, to name but a few.